Deep-learning segmentation of fascicles from microCT of the human vagus nerve - Buyukcelik, Ozge N.; Lapierre-Landry, Maryse; Kolluru, Chaitanya; Upadhye, Aniruddha R.; Marshall, Daniel P.; Pelot, Nicole A.; Ludwig, Kip A.; Gustafson, Kenneth J.; Wilson, David L.; Jenkins, Michael W.; Shoffstall, Andrew J. (Frontiers in Neuroscience, 2023)
Introduction MicroCT of the three-dimensional fascicular organization of the human vagus nerve provides essential data to inform basic anatomy as well as the development and optimization of neuromodulation therapies. To process the images into usable formats for subsequent analysis and computational modeling, the fascicles must be segmented. Prior segmentations were completed manually due to the complex nature of the images, including variable contrast between tissue types and staining artifacts. Methods Here, we developed a U-Net convolutional neural network (CNN) to automate segmentation of fascicles in microCT of human vagus nerve. Results The U-Net segmentation of 500 images spanning one cervical vagus nerve was completed in 24 s, versus 40 h for manual segmentation, i.e., nearly four orders of magnitude faster. The automated segmentations had a Dice coefficient of 0.87, a measure of pixel-wise accuracy, thus suggesting a rapid and accurate segmentation. While Dice coefficients are a commonly used metric to assess segmentation performance, we also adapted a metric to assess fascicle-wise detection accuracy, which showed that our network accurately detects the majority of fascicles, but may under-detect smaller fascicles. Discussion This network and the associated performance metrics set a benchmark, using a standard U-Net CNN, for the application of deep-learning algorithms to segment fascicles from microCT images. The process may be further optimized by refining tissue staining methods, modifying network architecture, and expanding the ground-truth training data. The resulting three-dimensional segmentations of the human vagus nerve will provide unprecedented accuracy to define nerve morphology in computational models for the analysis and design of neuromodulation therapies.